A dictionary-based comparative study of the Chinese “个 (gè)” and the Malay “buah” numeral classifiers - Ng, Chwee Fang; Awang, Sariyan; Yap, Ngee Thai (Universiti Malaysia Sarawak, 2024)
Classifiers are used for categorising nouns according to animacy, form, shape, and size. As one of the Austronesian languages, Malay is said to have an extensive numeral classifier system. Past studies have classified these two classifiers as general classifiers; however, an extensive study comparing the use of these two classifiers have not been attempted. This study aims to highlight the similarities and differences by comparing the Chinese classifier “个 (gè)” and the Malay “buah” using evidence from reference classifier dictionaries of the two languages. The findings show that while some similarities exist and both classifiers can be used interchangeably with some nouns, these classifiers are unique and have distinctive semantic usage. Both 个 (gè) and buah are used for organisation, products of nature, buildings and places, and artifacts (things created by humans). However, only 个 (gè) can be used for organs or body parts, humans, fruits and food, time, directions, and thought and intellectual products. In contrast, only buah is used for transportation, accessories, home furniture and appliances, publications, musical instruments, and performances.